Evaluasi laporan pelaksanaan tugas tenaga pengajar BIPA wilayah ASEAN 2 masa tugas 2015-2018 - indah okitasari (Badan Pengembangan dan Pembinaan Bahasa, 2019)
BIPA program is a program designed for foreigners to study the Indonesian language as well as the Indonesian culture. This study attempts to analyze the quality of the final report of BIPA teachers from 20152018 in ASEAN 2 (Timor Leste, Vietnam, and the Philippines). The author uses a descriptive qualitative research method to evaluate the 23 final reports of BIPA teachers based on the checklists. The instruments were adapted from the theories and the guidelines of BIPA reports made by PPSDk. The results of the study indicate that the quality of the teachers’ reports is already good, however, the reporting guidelines for the implementation of the BIPA teaching workforce need to be refined by adding the intercultural understanding concepts included in the report introduction section. Besides, to provide a good service, PPSDK should give an intercultural understanding for the teachers in special training. It is expected that this study will be significant to the field of intercultural communication and education in Indonesia.